THE INFLUENCE OF WORKING TIME ON CHANGES IN THE QUALITY OF CARS: WORKING CONDITIONS AND PATTERNS OF THEIR CHANGE (American Journal of Technology and Applied Sciences, 2024)
This article presents the development of a comprehensive theoretical framework, consisting of rules, to facilitate the interpretation and modeling of quality change processes in both individual cars and their collective groups. The emphasis is placed on ensuring adequacy in capturing the dynamic nature of these processes. A key feature of the framework is its incorporation of seasonal variations in working conditions and intensity. By considering these factors, the rules aim to enhance the understanding of how the quality of cars evolves over time, providing a valuable foundation for future research and practical applications in the automotive industry.